(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background: Self-rated health (SRH), as a powerful independent predictor of mortality, has been used worldwide. However, there is currently lack of information about the SRH in Iran as a developing country. This study was conducted to investigate the relationship between SRH and socioeconomic factors in the general population in western Iran. Methods: A cross-sectional study was conducted in 2017 enrolling 1,444 subjects aged 18 years and over in five areas of Kermanshah City, Iran. A single question of SRH with five scales of excellent (coded as 1), very good, good, fair, or poor (coded as 5) was used. Univariate and multiple logistic regression models were performed to determine factors associated with poor self-rated health. Results: The proportion of poor SRH was 14.7%. Multiple logistic regression showed that the most important determinants of poor SRH were older age (adjusted odds ratio (AOR)31-50year=1.96, AOR≥51year=4.93, married status (AOR=2.53), divorced or widowed status (AOR=2.62), self-reported income level as middle (AOR=2.51) and low (AOR=4.59), rural residency (AOR=1.5), low physical activity (AOR=11.97), and having chronic diseases (AOR=6.85). In addition, the educational level had a negative relationship with poor SRH (AOR academic=0.47). Conclusion: Our results revealed that both individual and social factors are directly associated with poor SRH. Therefore, these determinant factors should be considered in health policies and planning for promoting health and SRH in the west of Iran.